The Impact of Polyploidization on the Evolution of Weed Species: Historical Understanding and Current Limitations - Rutland, Claudia Ann; Hall, Nathan D.; McElroy, Joseph Scott (Frontiers in Agronomy, 2021)
Whole genome duplication via polyploidization is a major driver of diversification within angiosperms and it appears to confer the most benefit during times of rapid environmental change. Polyploidization offers expanded access to novel phenotypes that facilitate invasion of new environments and increased resistance to stress. These new phenotypes can arise almost immediately through the novel interactions among or between transcription factors of the duplicated genomes leading to transgressive traits, and general heterosis, or they can occur more slowly through processes like neofunctionalization, and subfunctionalization. These processes are characterized by the changes within homologs of the duplicated genomes, homoeologs. It has been proposed that redundant homoeologs are released from selective constraints and serve as an additional source of adaptive genetic variation, particularly in neo and meso-polyploids. Current practices in weed management create rapid environmental change through the use of chemicals, practices that are meant to cause the extirpation of the designated weed, and represent a strong recurrent selective event—a scenario that should favor polyploidy species. Here we ask the question, “Do polyploids make better weeds?”. It is our conclusion that such a question is impossible to answer at this time due to the lack of resources and understanding in weed genomics. The growing contingent of research in weed genomics, however, driven by herbicide resistance evolution is rapidly improving our understanding of weed molecular biology and will aid in improving understanding of the impacts of ploidy levels on weed evolution and adaptation in the future.